Analysis of consumption and spending with potentially hazardous medicines in a tertiary hospital of the northeast Brazil (Research, Society and Development, 2020)
The ABC curve has been widely indicated in order to achieve efficient management of medicines in stock, with the Potentially Hazardous Medicines (MPP's) group being responsible for a considerable demand within the hospital. This study aims to analyze the consumption and expenditure on standardized MPP's in a tertiary hospital in Northeastern Brazil using the ABC classification method. This is a descriptive and retrospective study, with quantitative and qualitative approach based on the analysis of data obtained from drugs transferred from the Pharmaceutical Supply Center (CAF), to the destination stock, Central Pharmacy, from March 2019 to August 2019. Items obtained after collection were categorized and classified according to the ABC curve. Data analysis was performed using descriptive statistics: frequency and percentage. The results showed that 11.50% of the items were categorized in class A and comprised 81.88% of the value, 15.40% of the items were classified in class B representing 12.76% of the expenses and 73.10% represented only 5.36% of the total cost, being listed in class C. The drugs that were in position A of the curve were: Heparin 5,000 IU / ml (0.25ml), Parenteral Nutrition Solutions (1000ml bag) and Enoxaparin 40mg / 0.4ml, representing respectively 30.25%, 28.36% and 23.18% of the percentage of the total amount spent. From the results obtained, it can be seen that MPP's generate significant financial impacts to hospital institutions, especially in the case of antithrombotic agents such as heparin and enoxaparin. The ABC classification therefore allows the priority items to be highlighted for cost management measures.